Brand Switching Konsumen Restoran Mie Pedas Di Kecamatan Denpasar Barat - Wijaya, Putu Teddy Bagas; Yoga, I Wayan Gede Sedana; Wiranatha , Anak Agung Putu Agung Suryawan; Sadyasmara, Cokorda Anom Bayu (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2025)
Spicy noodle restaurants succeeded in capturing consumer attention by offering uniquely flavored noodles distinctive. The objective of this study are to identify the characteristics of consumers of spicy noodle, to analyze brand switching behavior in the spicy noodle market from the present time up until the fifth year, and to determine the long-term market share equilibrium of various spicy noodle brands in the West Denpasar District. The method employed is the Markov Chain analysis, processed using Microsoft Excel 2021. The sample size was determined using the Cochran formula, resulting in 100 respondents. The findings indicate that the majority of respondents who consume spicy noodle products are female, predominantly aged between 21–25 years. Approximately 54% of respondents are students with monthly expenditure on food ranges between IDR 100,000 and IDR 999,000, with an average consumption frequency of 2–3 times per month. In the first year (2025), the market share of spicy noodle brands was distributed as follows: Mie Kober (19%), Mie Gacoan (49%), and Wizzmie (32%). In the second year (2026), Mie Kober and Mie Gacoan experienced a decline in market share to 16.72% and 44.31% respectively, while Wizzmie saw an increase to 38.97%. In the third year and subsequent periods, fluctuations in market share occurred across all brands, in which the market shares in the fifth year (2029) are Mie Kober (14.83%), Mie Gacoan (41.82%) and Wizzmie (43.36%). The market shares are projected to stabilize by the 11th year, with Mie Kober at 14.67%, Mie Gacoan at 41.69%, and Wizzmie at 43.65%